EPISTEMOLOGY OF GENDER JUSTICE: A THEMATIC INTERPRETATION TO DECONSTRUCT PATRIARCHAL READINGS - Purnamasari, Elvira; Wati, Devi Setia; Agustini, Agustini (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
Gender justice remains a central discourse in contemporary Islamic studies, particularly in societies where patriarchal cultural norms are often legitimized through rigid and atomistic interpretations of Qur’anic texts. This study examines the epistemology of gender justice in the Qur’an by employing thematic interpretation (tafsir maudhu’i) as a methodological tool to deconstruct patriarchal readings of equality verses. Using qualitative library research, this study integrates Bayani (textual–linguistic), Burhani (rational–sociological), and Irfani (ethical–spiritual) epistemologies to analyze selected Qur’anic verses, including QS. An-Nahl: 97, QS. Ali ‘Imran: 195, QS. An-Nisa: 124, and QS. Al-Hujurat: 13. The findings demonstrate that the Qur’an consistently affirms the fundamental equality of men and women in creation, spiritual responsibility, and divine reward. Patriarchal bias arises not from the Qur’anic text itself, but from ahistorical and partial interpretive frameworks. This study contributes an integrated Bayani–Burhani–Irfani (BBI) epistemological model as a systematic approach for gender-just Qur’anic interpretation within contemporary Islamic thought.